2016
DOI: 10.1007/s00226-016-0803-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of wood-based panels: specific heat determination

Abstract: Ensuring reliability of data on thermal properties of wood-based panels is important for manufacturing processes, especially when it is recommended to shorten the cooling phase and stack the panels in hot conditions. Prediction of the heat transfer during cooling phase and normal or hot stacking based on accurate data is essentially important for attaining panels of required properties. The thermal properties are also required when designing houses, especially low-energy or passive ones. Therefore, a water cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…The specific heat was firstly measured with a DSC system, and the obtained results were used for the inverse identification of the thermal conductivity as a function of temperature. The present study exploited the same methodology and the results of the specific heat measurements as reported by Czajkowski et al (2016) were used for determining the thermal conductivity with the inverse method. It was assumed that due to the space orientation of strands, particles or fibers in wood-based panels, the inplane thermal conductivities have to be similar and it was postulated in the present study to regard the in-plane values of the property as equal.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The specific heat was firstly measured with a DSC system, and the obtained results were used for the inverse identification of the thermal conductivity as a function of temperature. The present study exploited the same methodology and the results of the specific heat measurements as reported by Czajkowski et al (2016) were used for determining the thermal conductivity with the inverse method. It was assumed that due to the space orientation of strands, particles or fibers in wood-based panels, the inplane thermal conductivities have to be similar and it was postulated in the present study to regard the in-plane values of the property as equal.…”
Section: Resultsmentioning
confidence: 99%
“…for a density of 660 kg/m 3 , specific heat of 1500 J/(kg K), and thermal conductivity equal to 0.12 W/(m K) as determined at a temperature of 20.3°C. The OSB thermal properties of the present study consisted of the following values: density of 619 kg/m 3 , specific heat of 1552 J/(kg K) as reported by Czajkowski et al (2016) and the identified in-plane and transverse thermal conductivity parameterized by Eq. (5) with coefficients given in Table 2.…”
Section: Validation Of Identificationmentioning
confidence: 99%
See 3 more Smart Citations